Characterization of the pilosebaceous microbiota and biofilm-forming capacity of bacteria isolated from patients with severe acne vulgaris - Từ, Mậu Xương; Phạm, Yến Nhi; Trần, Hữu Hậu; Nguyễn, Ngọc Thạnh; Bùi, Hoàng Đăng Long; Trần, Ngọc Dung; Huỳnh, Xuân Phong (Hue University Journal of Science: Natural Science, 2026)
Acne vulgaris is a chronic inflammatory dermatological condition influenced by multiple factors, including endocrine dysregulation, immune responses, genetic predisposition, and particularly the skin microbiota. Dysbiosis within the pilosebaceous unit may exacerbate disease severity, in which biofilm formation plays a crucial role by promoting bacterial persistence and reducing antibiotic efficacy. This study aimed to isolate and characterize bacterial species inhabiting the pilosebaceous unit in patients with severe acne, as well as to evaluate the biofilm-forming capacity of the isolated strains. Clinical samples were cultured under anaerobic conditions, and bacterial identification was performed using 16S rRNA gene sequencing. A total of 24 bacterial isolates were obtained, with the genus Cutibacterium predominating (70.8%), including C. acnes (50%), C. avidum (12.5%), and C. granulosum (8.3%). Additionally, members of the family Enterobacteriaceae (12.5%) and other species such as Bacillus spp., Lactiplantibacillus plantarum, and Levilactobacillus brevis were detected. All C. acnes isolates exhibited biofilm-forming ability, with strain Sn9-2 demonstrating the strongest capacity. These findings highlight the predominance of Cutibacterium, particularly biofilm-forming strains, in severe acne, and underscore the potential role of biofilms in disease persistence and reduced treatment responsiveness.